Pengaruh Jumlah Uang Beredar dan Suku Bunga Terhadap Tingkat Inflasi di Indonesia - Fachrul Dena; Asep Setiyawan; Fitriani Fitriani; Ingka Rizkia Gusdinar (Jurnal Pendidikan Ekonomi Indonesia, 2021)
This study discusses the factors that cause the rate of inflation. This research focuses on discussing the influence of the money supply and interest rates on the inflation rate in Indonesia. The purpose of this study was to describe the effect of the money supply and interest rate variables on inflation using multiple linear regression analysis using the OLS method as the method in this study. The results of this study indicate that the money supply has a significant effect on the inflation rate and interest rates have no significant effect on the inflation rate